2009
DOI: 10.1007/s10461-009-9523-4
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision and HIV Prevention: Looking to the Future

Abstract: Now that male circumcision has been shown to have a protective effect for men against HIV infection when engaging in vaginal intercourse with HIV-infected women, the research focus needs to shift towards the operational studies that can pave the way for effective implementation of circumcision programs. Behavioral research is needed to find out how people perceive the procedure and the barriers to and facilitators of uptake. It should also assess the risk of an increase in unsafe sex after circumcision. Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…These factors subsequently become obstacles that undermine the uptake of VMMC. Although similar to findings reported elsewhere (see Brooks et al, 2010;Khumalo-Sakutukwa et al, 2013), this paper provides a comprehensive qualitative picture of barriers to VMMC from the perspective of uncircumcised males, while previous studies of VMMC in Zimbabwe were often heavily biased towards quantitative methods (Hatzold et al, 2014). By utilising purely qualitative methods, this study provides a rich picture of feelings and attitudes towards VMMC among men across various age categories.…”
Section: Discussionsupporting
confidence: 71%
“…These factors subsequently become obstacles that undermine the uptake of VMMC. Although similar to findings reported elsewhere (see Brooks et al, 2010;Khumalo-Sakutukwa et al, 2013), this paper provides a comprehensive qualitative picture of barriers to VMMC from the perspective of uncircumcised males, while previous studies of VMMC in Zimbabwe were often heavily biased towards quantitative methods (Hatzold et al, 2014). By utilising purely qualitative methods, this study provides a rich picture of feelings and attitudes towards VMMC among men across various age categories.…”
Section: Discussionsupporting
confidence: 71%
“…Social support, specifically support from parents, friends, and sexual partners, was strongly associated with a Swazi man's intention to become circumcised. Previous research indicates that social networks and norms can act as important determinants of individual behavior, increasing the likelihood of VMMC being promoted as a form of HIV prevention (Brooks et al, 2010;Herman-Roloff, Otieno, et al, 2011;Montaño et al, 2014;Peltzer & Mlambo, 2012). Indeed, health decisions can be made easier if one has the full support of friends and family members.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, mounting evidence has indicated the potential of voluntary medical male circumcision (VMMC) to reduce the risk of HIV infection for men (Auvert et al, 2005;Bailey et al, 2007;Brooks et al, 2010;Gray et al, 2007;Londish & Murray, 2008;Lukobo & Bailey, 2007;Tarimo et al, 2012;Templeton, 2010). Randomized controlled trials (RCTs) in South Africa, Kenya, and Uganda have demonstrated up to 60% reduction in HIV infection rates among circumcised men compared to uncircumcised men (Auvert et al, 2005;Bailey et al, 2007;Brooks et al, 2010;Gray et al, 2007;Londish & Murray, 2008;Lukobo & Bailey, 2007;Tarimo et al, 2012;Templeton, 2010).…”
Section: Informing the Scaling Up Of Voluntary Medical Male Circumcismentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lower than anticipated uptake of the VMMC approach, conversations have surfaced that suggest different messages are needed to address varying social groups and their unique concerns (Brooks et al 2010; Gilliam et al 2010; Sgaier et al 2014). While tailored framing may prove useful in providing relevant and compelling information to convince the public of the advantages of VMMC (Brooks et al 2010; Gilliam et al 2010), this approach anticipates that individuals will act upon scientific evidence, has limited concern for alternative practices, rationalities, or barriers, and fails to consider that people employ multiple logics when avoiding risk.…”
Section: Introducing and Re-introducing Male Circumcisionmentioning
confidence: 99%